1998
DOI: 10.1097/00007632-199801010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment of Whiplash Neck Sprain Injuries

Abstract: The outcome was better for patients who were encouraged to continue engaging in their normal, pre-injury activities as usual than for patients who took sick leave from work and who were immobilized during the first 14 days after the neck sprain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(28 citation statements)
references
References 14 publications
2
22
0
4
Order By: Relevance
“…It is documented that decreased activity after a MVC increases the risk of chronic WAD, 43 but the mechanisms by which decreased activity influences skeletal muscle structure and function following whiplash are largely unknown. The effect of depriving healthy individuals from their normal daily activity (as may be expected to occur if an individual reduces normal activity after a whiplash injury) can lead to fatigue, mood swings, reductions in muscle volume and intramuscular fatty infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…It is documented that decreased activity after a MVC increases the risk of chronic WAD, 43 but the mechanisms by which decreased activity influences skeletal muscle structure and function following whiplash are largely unknown. The effect of depriving healthy individuals from their normal daily activity (as may be expected to occur if an individual reduces normal activity after a whiplash injury) can lead to fatigue, mood swings, reductions in muscle volume and intramuscular fatty infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Although gender was unknown for porcine donors in the present study, based upon results of previous experimental mechanical studies, it remains unlikely that this factor would have significantly affected physiological or rupture arterial mechanics. However, continued studies of gender effects on soft-tissue material properties are warranted due to differences in arterial trauma rates cited above, as well as other soft-tissue injury modalities wherein gender discrepancies are clinically and epidemiologically identified [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…These included educational booklets (for mechanical neck disorder; Glossop et al 1982 [52]), advice on acting as usual and instructions for self-training exercises to be initiated immediately (for acute WAD [53]) and mobilization advice (for acute WAD [54]). Advice on activation given through these modes showed low or very low evidence of benefit when compared to teaching exercises alone (for short-term pain and knowledge (Glossop et al 1982 [52]), immobilization (for short- and intermediate-term pain, range of motion and cognitive symptoms [53] and physiotherapy or rest (for short-term pain and long-term presence of symptoms [54]. …”
Section: Evidence Of Benefitmentioning
confidence: 99%
“…The research also showed low GRADE evidence of no difference (1 trail, 211 participants, Borchgrevink et al 1998 [53]) when comparing the use of a collar versus advice to “act as usual” for immediate, short-term or intermediate-term pain relief, global perceived effect, improving ROM, or time on sick leave. Also there was not difference in pain at the short- and intermediate-term follow-up if a collar was worn 2 days versus 7 days (1 trials, 70 participants, Dehner et al , 2006 [92]).…”
Section: Low or Very Low Evidencementioning
confidence: 99%
See 1 more Smart Citation